Factors affecting on bond strength of glass fiber post cemented with different resin cements to root canal - Clavijo, V. R. G. [UNESP]; Bandeca, Matheus Coelho [UNESP]; Calixto, L. R. [UNESP]; Nadalin, M. R.; Saade, E. G. [UNESP]; Oliveira-junior, O. B. [UNESP]; Andrade, M. F. [UNESP] (Maik Nauka/interperiodica/springer, 2009)
Luting materials provides the retention of endodontic post. However, the failures of endodontic posts predominantly occurred are the losses of retention. Thus, the alternating use to remove the smear layer, open the dentine tubules, and/or etch the inter-tubular dentine can be provided by EDTA. This study was performed to evaluate effect of EDTA on bond strength of glass fiber post cemented with different resin cements to root canal. Fifty bovine incisors were selected and the crowns were removed to obtain a remaining 14-mm-height root. The roots were randomly distributed into five groups: GI: RelyX (TM) ARC/LED; GII: RelyX (TM) U100/LED; GIII EDTA/RelyX (TM) U100/LED; GIV: Multilink (TM); and GV: EDTA/Multlink (TM). After endodontic treatment, the post space was prepared with the drills designated for the quartz-coated-carbon-fiber post Aestheti-PostA (R). Before application of resin cements, root canals were irrigated with 17% EDTA (GIII and GV) during 1 min, rinsed with distilled water and dried using paper points. The light-cured materials were light-activated with UltraLume LED 5 (Ultradent, South Jordan, Utah) with power density of 1315 mW/cm(2). Specimens were perpendicularly sectioned into approximately 1 mm thick sections and the stubs were performed on Universal Testing Machine. The analysis of variance (ANOVA) and Tukey's post-hoc tests showed significant statistical different between RelyX (TM) ARC (GI) and RelyX (TM) U100 independent of the pre-treatment (GII to GIII) (P < 0.05). The Multlink (TM) showed between RelyX (TM) ARC and RelyX (TM) U100 (GI to GIII; GII to GV) (P < 0.05). The ANOVA showed significant statistical similar (P > 0.05) to all resin cements between the Cervical to Apical regions (GI to GV). The use of 17% EDTA showed no difference significant between the resin cements evaluated (GII to GIII; GIV to GV). Within the limitations of the current study, it can be concluded that the use of EDTA did not provide efficiency on bond strength. The RelyX (TM) ARC showed higher bond strength values than RelyX (TM) U100.